Manejo de la calidad en el racimo de banano orgánico con dos sistemas de cirugía y tres de protección - Gorotiza Mena, Humberto Carlos (2009)
In the Farm Santa Inés, property of Technical University of Machala of the canton Machala of the county of The Gold, was investigated on the Handling of the quality in the banana tree cluster with two surgery systems and three of protection, with the following objectives: 1. To determine which of the protection systems better quality is obtained in banana tree clusters; 2. To carry out an analysis of box yield for organic hectare. It was compared the new systems of protection of the cluster like the employment of suspenders Banalastic and Daipas of foam, and the surgery of the lateral fingers of the second hand, in front of the polyethylene Daipas with and without surgery that you/they are at the present time the systems of more employment. The design statistical employee for the interpretation of the results gathered in the field was that of Blocks at random with six treatments and ten clusters for treatment Of the analysis of the results he/she comes off that the implementation of technical of protection of the cluster to improve the quality of the fruit and the goods of the treatments in the variables: weight of hands, ratio and yield didn't end up being superior that the organic witness, this is polyethylene Daipas without surgery of lateral fingers. The most consistent indicator that demonstrated the advantage of the protection of the hands of the clusters with suspenders Banalastic and Daipa of foam was the number of Cluster, in which you reports an increment from the 23 %. The erosion and yield was higher in the witness Daipas of polyethylene without surgery. The grade of the clusters, they were homogeneous and the crop like the final quality of the fruit doesn’t end up varying significantly with regard to the witness.